In silico enzyme screening identifies an SDR ketoreductase from Thermus caliditerrae as an attractive biocatalyst and promising candidate for protein engineering - Sosa, Yvett; Kapur, Bhav; Hurtak, Jessica; Kingsley, Laura J.; Wu, Hao; Gruber, Stefanie; Nar, Herbert; Khattabi, Saad; Moral, Jesus Seco; Lucas, Maria Fátima; Martin, Caterina; Lončar, Nikola; et al. (Frontiers in Chemical Biology, 2024)
Biocatalysis, particularly through engineered enzymes, presents a cost-effective, efficient, and ecofriendly approach to compound synthesis. We sought to identify ketoreductases capable of synthesizing optically pure alcohols or ketones, essential chiral building blocks for active pharmaceutical ingredients. Using BioMatchMaker®, an in silico high-throughput platform that allows the identification of wild-type enzyme sequences for a desired chemical transformation, we identified a bacterial SDR ketoreductase from Thermus caliditerrae, Tcalid SDR, that demonstrates favorable reaction efficiency and desired enantiomeric excess. Here we present two crystal structures of the Tcalid SDR in an apo-form at 1.9 Å and NADP-complexed form at 1.7 Å resolution (9FE6 and 9FEB, respectively). This enzyme forms a homotetramer with each subunit containing an N-terminal Rossmann-fold domain. We use computational analysis combined with site-directed mutagenesis and enzymatic characterization to define the substrate-binding pocket. Furthermore, the enzyme retained favorable reactivity and selectivity after incubation at elevated temperature. The enantioselectivity combined with the thermostability of Tcalid SDR makes this enzyme an attractive engineering starting point for biocatalysis applications.